The Health Belief Model in the Context of Alcohol Protective Behavioral Strategies. Issue 1 (2nd January 2023) - De Leon, Ardhys N.; Peterson, Roselyn; Dvorak, Robert D.; Leary, Angelina V.; Kramer, Matthew P.; Burr, Emily K.; Toth, Ethan M.; Pinto, Daniel
Abstract : Objective : Alcohol use continues to be prevalent and problematic among young adult samples. Protective behavioral strategies (PBS), which are harm reduction strategies utilized while drinking, have been linked to decreased alcohol use and subsequent alcohol-related problems. An individual's likelihood of adopting PBS and other health behaviors, according to The Health Belief Model (HBM), is dependent on perceived susceptibility to and severity of adverse health outcomes, as well as perceived benefits and barriers related to implementing those behaviors. The present study examined whether the perceived effectiveness of PBS in the context of the HBM leads to an increase in PBS use. Method : The analytic sample ( n =694 college students, M age =20.21, SD =4.37, 63.26% female, 72.05% Caucasian) self-reported demographics, weekly alcohol consumption (i.e., frequency, intensity, and quantity), alcohol-related problems, use of PBS, and perceived effectiveness of PBS use. A latent variable model was used to test the effect of perceived PBS effectiveness on PBS use, alcohol consumption, and alcohol-related problems. Results : Perceived PBS effectiveness was associated with a higher likelihood of using PBS subtypes (Manner of Drinking, Stopping/Limiting Drinking, and Serious Harm Reduction), which in turn was associated with reductions in alcohol consumption and problems. Conclusions : These findings suggest that increasing perceptions of PBS effectiveness may lead to more PBS use, decreased alcohol consumption, and fewer alcohol-related problems. Future research could implement longitudinal methodology to assess attempts to increase perceived effectiveness of PBS use and potentially establish a causal link between these perceptions, PBS use, and alcohol-related outcomes.